Long walk from volkekunde to anthropology: reflections on representing the human in South Africa - van der Waal, C.S. (Kees) (Anthropology Southern Africa, 2015)
This paper stems from a seminar that the author gave at his retirement from the Department of Sociology and Social Anthropology at Stellenbosch University earlier in 2015. It details his long personal, political and intellectual journey from volkekunde to social anthropology. Written in the register of historical auto-ethnography, the piece details his theoretical paradigm shift and intellectual interlocutors in the process, while also pointing at the important role that he played in the transformation and expansion of social anthropology at both Rand Afrikaans University (now the University of Johannesburg) and at Stellenbosch University.